The recontextualisation of values in the multilingual workplace. (7th August 2017) - Bjørge, Anne Kari; Sandvik, Alexander Madsen; Whittaker, Sunniva
Abstract : Purpose: The purpose of this paper is to explore how corporate values are interpreted by local and international employees in a multilingual organisation that has opted for the local language, not English, as its corporate language. Design/methodology/approach: This is a research paper exploring how the recontextualisation and resemiotisation of value terms impact on how corporate values are interpreted, employing triangulation of questionnaire and interview results. Findings: When values are recontextualised in employee discourse, proficiency in the corporate language and cultural background was found to have an impact on their interpretation. Internationals were found to have a broader and not exclusively professional interpretation compared to the locals. Internationals with a low level of proficiency in the local language were more sceptical than the locals as to whether there was a shared understanding of the values. Research limitations/implications: The questionnaire yielded fewer respondents than the authors expected, which should be taken into account when interpreting the results. Practical implications: The paper suggests best practices for communicating corporate values to a multilingual workforce. Social implications: This paper contributes to the understanding of linguistic challenges in the multilingual work contexts. Originality/value: To the authors' knowledge, there is little prior in-depth research on how language impacts on employees' interpretation of corporate values. As values are cohesive devices in organisations, the language used to convey them is worth addressing as the present paper aims to demonstrate.